Tracking down gene intefrity within fragile sites: Do they play a role in oesoplageal cancer? - Brown, Jacqueline (My University, 2006)
Oesophageal cancer (OC) is the third most common malignancy in South Africa (SA), affecting 1 in 20 and 1 in 76 black males and females respectively. Squamous cell carcinoma (SSC) is an aggressive disease showing a poor prognosis due to late diagnosis. Identification of genetic changes associated with these tumours may shed light on its pathophysiology and aetiology in SA. The chromosomal status of five OC cell lines, established in SA, was assessed to identify possible common chromosomal alterations by M-FISH (multicolour fluorescence in situ hybridisation) and specifically the fragile site loci, FRA3B and FRA16D by FISH (Fluorescence in situ hybridisation). The genes at these loci, FHIT (Fragile Histidine Triad) and WWOX (WW domain containing oxidoreductase) respectively, were analysed by RT-PCR (Reverse transcriptase polymerase chain reaction). FHIT was aberrantly expressed in four of the five cell lines while WWOX expression was normal. The EGFR (epidermal growth factor receptor) locus is frequently amplified and this gene is also over-expressed in OC. Increased EGFR expression was previously found in three of the cell lines, for this reason, particular attention was paid to markers involving the EGFR locus on 7p. An interesting marker chromosome seven was identified in one of the cell lines and further analysis, using a specific EGFR probe, revealed an amplification unit involving EGFR in this cell line. Common translocations involving chromosomes 3 and 1 as well as 3 and 22 were identified in two cell lines; these may involve a locus involved in OC and warrants further investigation.
Faculty of Science School of Pathology 9900713m Cell #: 083 718 9093
Keywords: Fargile sites; Oesophageal cancer